SPECTRUM AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF SECONDARY BACTERIAL INFECTIONS IN EXTRAPULMONARY TUBERCULOSIS: A CROSS-SECTIONAL OBSERVATIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Extrapulmonary tuberculosis (EPTB) is a significant contributor to global morbidity. Secondary bacterial infections complicating EPTB lesions are understudied but can alter disease progression, delay clinical recovery, and accelerate antimicrobial resistance. Aim & Objectives: To determine the burden, bacterial spectrum, and antimicrobial susceptibility patterns of secondary bacterial infections in patients with EPTB, and to identify associated host-related factors. Methods: A hospital-based cross-sectional observational study was conducted at the Microbiology Laboratory of CRGH Hospital and Ruxmani Ben Deep Chand Gardi Medical College, Ujjain, India, from March 2023 to July 2025. Clinical samples (pus, pleural fluid, and tissue biopsies) from 67 EPTB patients were analyzed using standard phenotypic microbiological and antimicrobial susceptibility testing (AST) methods. Statistical associations were evaluated using Fisher’s exact test. Results: Secondary bacterial infections were confirmed in 7 of 67 patients (10.4%; 95% CI: 5.2–20.0%). The isolated pathogens were Klebsiella pneumoniae (n=3; 42.8%), Pseudomonas aeruginosa (n=2; 28.6%), and Staphylococcus aureus (n=2; 28.6%). Most isolates were recovered from pus samples (n=5; 8% of total pus specimens). All three K. pneumoniae isolates were multidrug-resistant (MDR, 100%), including one extensively drug-resistant (XDR, 33.3%) strain and two extended-spectrum β-lactamase (ESBL) producers (66.6%). Both S. aureus isolates were confirmed as methicillin-resistant S. aureus (MRSA) and were MDR (100%). Conversely, P. aeruginosa isolates remained fully susceptible to core anti-pseudomonal agents. No statistically significant associations were found between infection status and age, gender, behavioral habits, or comorbidities, though higher rates were observed in patients aged 45–60 years, diabetics, and chronic kidney disease (CKD) patients. Conclusion: Secondary bacterial infections in EPTB are heavily dominated by highly resistant opportunistic pathogens like MRSA and ESBL/MDR K. pneumoniae. Routine microbiological surveillance and targeted antimicrobial stewardship are vital to optimizing therapeutic outcomes in EPTB co-infections.